PENGAWETAN LIMA JENIS KAYU DENGAN KOPPERS FORMULA 7 MENURUT METODE PENCELUPAN - Barly Barly; Pipin Permadi (Jurnal Penelitian Hasil Hutan, 1987)
Five timber species were treated  with Koppers Formula  7 using momentary   immersion  method.   The samples (5 cm x 5 cm x 100 cm)  were then introduced  into a diffusion chamber for  one, three, or jive  weeks. The depth of penetration  was measured after cutting the samples and result analyzed.  The conclusions are :The duration  of diffusion  has a highly significant  effect  on preservative penetration,   while the timber species did not have a significant  bearing in the penetration.   The rate of diffusion   is proporsional  to the treatment  time.Taking  the forgoing result into account,  the moisture  content  has no effect  on the depth  of penetration.The momentary   immersion  method  appeared  to have met  to the standar  requirement  for  all timber species tested  in this experiment.The result indicated that duration  in one week gives statisfactory  penetration  for  the mahoni,  manii and jeungjing  species.  The durian  and petai however,  could  only give statisfactory   results when  the duration  is longer than  three  weeks